Magi : the labyrinth of magic. 23 - Otaka, Shinobu (VIZ Media, 2017)
An epic dungeon-busting adventure inspired by One Thousand and One Nights! Deep within the desert lie the mysterious Dungeons, vast stores of riches there for the taking by anyone lucky enough to find them and brave enough to venture into the depths from where few have ever returned. Plucky young adventurer Aladdin means to find the Dungeons and their secrets, but Aladdin may be just as mysterious as the treasures he seeks. Aladdin tells the story of the fallen Alma Tran. In the distant past, in another world, humanity struggled to survive an onslaught of monsters, but once united against them, human sorcerers became as bad as the enemies they once fought. Solomon himself struggled to lead humanity up out of the darkness it had created, but with every victory comes sacrifice...